A Randomized Controlled Trial of Four Precolonoscopy Bowel Cleansing Regimens - Dina Kao; Eoin Lalor; Gurpal Sandha; Richard N Fedorak; Bloeme van der Knoop; Stieneke Doornweerd; Harmke van Kooten; Eline Schreuders; William Midodzi; Sander Veldhuyzen van Zanten (Canadian Journal of Gastroenterology, 2011)
BACKGROUND: The ideal bowel cleansing regimen for colonoscopy has yet to be determined.